Analisis Klausa Verbal dalam Teks Deskripsi pada Buku Pendidikan Pancasila dan Kewarganegaraan Kelas X SMA/SMK Kurikulum Merdeka - Lalitta Octavia; Vianni Nifattien Vrisna Putri; Novana Ika Puspita; Elvina Amanda Cahya Dewi; Asep Purwo Yudi Utomo; Didi Pramono (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research is an activity to examine descriptive texts that focus on the area of syntax, which is called verbal clauses. The texts analyzed are descriptive texts about the concept, its importance, and examples of mutual cooperation practices. This research is motivated by the diversity of the use of verbal clauses in descriptive texts. The purpose of this study is to provide insight into the classification of verbal clauses and provide examples of their classification in the descriptive text in the